2012
DOI: 10.1148/radiol.12111916
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Shift MR Imaging Methods for the Quantification of Transcatheter Lipiodol Delivery to the Liver: Preclinical Feasibility Studies in a Rodent Model

Abstract: Purpose:To demonstrate the feasibility of using chemical shift magnetic resonance (MR) imaging fat-water separation methods for quantitative estimation of transcatheter lipiodol delivery to liver tissues. Materials and Methods:Studies were performed in accordance with institutional Animal Care and Use Committee guidelines. Proton nuclear MR spectroscopy was first performed to identify lipiodol spectral peaks and relative amplitudes. Next, phantoms were constructed with increasing lipiodol-water volume fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Proton ( 1 H) NMR spectroscopy revealed that the spectrums of both native LPD and newly formulated RIO were almost identical ( Fig. 1B) and similar to that previously reported for LPD (Yin, 2012).…”
Section: Characterization Of Red Iodized Oil Dye (Rio)supporting
confidence: 84%
“…Proton ( 1 H) NMR spectroscopy revealed that the spectrums of both native LPD and newly formulated RIO were almost identical ( Fig. 1B) and similar to that previously reported for LPD (Yin, 2012).…”
Section: Characterization Of Red Iodized Oil Dye (Rio)supporting
confidence: 84%
“…However, the signals in its 1 H NMR spectrum can be used to identify its presence in the polymer clips. The characteristic peaks at 0.96 ppm, 2.25 ppm, and 4.27 ppm have been used to distinguish Lipiodol from the polymers in the clip formulation . NMR analysis of the markers also confirmed the presence of Lipiodol remaining in the samples after 6 months.…”
Section: Resultsmentioning
confidence: 86%
“…The characteristic peaks at 0.96 ppm, 2.25 ppm, and 4.27 ppm have been used to distinguish Lipiodol from the polymers in the clip formulation. 16 NMR analysis of the markers also confirmed the presence of Lipiodol remaining in the samples after 6 months. However, 1 H NMR splitting of the polymer and Lipiodol could not be determined in the marker samples because of excess dissolved tissue samples along with iron oxide nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A few studies have reported that this new technology makes it possible to discriminate the signals obtained in Lipiodol accumulation in HCCs [20][21][22] . In the present study, we therefore investigated whether chemical-shift MRI could be used to evaluate the signal derived from Lipiodol accumulation in HCCs after Lp-TACE.…”
Section: Originalmentioning
confidence: 99%